Mission to Mars. Reliable method for liquid solutions diagnostics - Krapivin, Vladimir F.; Varotsos, Costas A.; Soldatov, Vladimir Y. (Frontiers in Environmental Science, 2014)
Manned mission to Mars aims at solving many problems associated with operational diagnostics of liquid solutions (including drinking water), medical issues, and liquid fuels. This paper mainly proposes a new method to solve these problems both during the flight and the stay on the surface of the planet. The proposed method consists of a database development of spectral images of liquid solutions supplied by a multiple-channel spectroellipsometer and the diagnostics of liquid solutions using this database. In addition, the process of learning and the expert system for adaptive recognition of liquid solutions is described. Finally, the test of the expert system is demonstrated for a series of liquid solutions.